Multimodality and children’s participation in classrooms: instances of research - Newfield, Denise (Faculty of Education, University of the Free State, 2011)
This paper describes how language and literacy classrooms became more participatory, agentive spaces through addressing a central issue in teaching and learning: the forms of representation through which children make their meanings. It reconsiders pedagogic research in under-resourced Gauteng classrooms during the period 1994 – 2005, during the first decade of education in post-liberation South Africa. This research shows teachers using multimodality in productive, expressive and creative ways that work against deficit models of children, drawing on their everyday experiences and their existing representational resources. It outlines the theoretical framework supporting the pedagogical approach, that of multimodal social semiotics, known more widely as “multimodality”, and discusses three instances of children’s multimodal practice, in Grades 1 and 2, 7 and 10 respectively. It sums up the role played by multimodality in participation, showing how multimodality enables cognitive, social and affective participation through expanding the semiotic space of the classroom and reconstituting the children as sign-makers.
Keywords: Participation; Classrooms; Multi-modality; Multi-modal pedagogies; Forms of representation; Learning; Semiosis; Sign-makers; Agency